99.4k views
2 votes
3(x - 3) - (6x - 3) = 4(3)

User Idoby
by
5.6k points

2 Answers

2 votes

Answer:

x=-6

Explanation:

*instead of doing a bunch of subtraction make it +(-#) you'll see what i mean

3(x - 3) - (6x - 3) = 4(3)

first do distributive property and figure out the easy stuff:

3x+(-9)+(-6x)+3=12

then you add 3x and 6x while also adding 9+3

-3x+(-6)=12

add +6 to both sides

-3x=18

then divide by -3

x=-6

User Chris Mohr
by
5.0k points
1 vote

Hey there!

3(x - 3) - (6x - 3) = 4(3)

3(x) + 3(-3) - 1(6x -3) = 4(3)

3(x) + 3(-3) -1(6x) -1(-3) = 4(3)

3x - 9 - 6x + 3 = 4(3)

-3x - 6 = 12

ADD 6 to BOTH SIDES

-3x - 6 + 6 = 12 + 6

CANCEL out: -6 + 6 because that gives you 0

KEEP: 12 + 6 because it helps solve for the x-value

-3x = 12 + 6

-3x = 18

DIVIDE -3 to BOTH SIDES

-3x/-3 = 18/-3

CANCEL out: -3/-3 because that gives you 1

KEEP: 18/-3 because it gives you the result of the x-value

x = 18/-3

18/-3 = x

SIMPLIFY IT!

x = -6

Therefore, your answer is: x = -6

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

User Byron Hawkins
by
6.0k points